Impact of entrepreneurship education on the entrepreneurship career intentions of university students. Case of Midlands State University - Tanaka T T Mutero; Blessed Mveku; Eukael Mbuyisa; Thelma E R Manhiwa; Lilian Gumbo (International Journal of Humanities and Social Science Research, 2022)
Entrepreneurship plays a significant role in the economic development of society. This is the reason why universities are paying attention to promoting entrepreneurship education programs. These programs are being provided at numerous levels and there is a need to assess the effectiveness of these programs from different aspects and to find out the strategies for designing entrepreneurship education programs more effective in terms of creating more student entrepreneurs. In order to know the effectiveness of entrepreneurship education, entrepreneurship intention plays a pivotal role. If students develop their intention to start their own venture in business, then it will be a good indicator of their future entrepreneurial behavior. Hence the current research examines the impact of entrepreneurship education in terms of entrepreneurship intention. The research had three objectives which are, to determine the impact of attitude has on entrepreneurship intentions, to determine the impact of subjective norms has on entrepreneurship intentions and to determine the impact of perceived behavioral control has on entrepreneurship intentions. As these three variables are relevant for developing the entrepreneurial intention hence it is was important to explore their mediating roles. In order to collect data, the questionnaire method was used and overall one hundred and thirty two questionnaires were included in the final data analysis. The results suggest that attitude, subject norm and perceived behavioral control directly impact on entrepreneurial intention. The study recommended the use of role models in entrepreneurship education as it influences student attitude, the adoption of Project-based learning as it explains well why people should be entrepreneurial and the need for student motivation.